2018
DOI: 10.1002/cphc.201800335
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Azeotrope Formation from Protic Ionic Liquids

Abstract: Herein, we present experimental evidence that protic ionic liquids (PILs), derived from 1 : 1 liquid mixtures of the organic superbases 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) with carboxylic acids, form azeotropic mixtures with acid/base molar fractions different from 1 : 1. The ability of the carboxylic acids to form strong hydrogen bonds with the PIL ion pair leads to an azeotropic composition richer in the acid component. The results show that the azeotropic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…The mechanism of evaporation was explained by the initial dissociation (de-ionization) of the ionic compounds into neutral acid and base, [BH] (Ribeiro et al 2017). Interestingly, although the acid has a higher volatility than the base, it was found that the base is more prone to vaporization from concentrated solutions (Ribeiro et al 2018;Ahmad et al 2016). This is a result of the tendency of the acid to form hydrogen bonds with the IL in the liquid phase, protecting it from vaporization (Ribeiro et al 2018).…”
Section: Properties Of Superbase-based Ils During Thermal Recoverymentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism of evaporation was explained by the initial dissociation (de-ionization) of the ionic compounds into neutral acid and base, [BH] (Ribeiro et al 2017). Interestingly, although the acid has a higher volatility than the base, it was found that the base is more prone to vaporization from concentrated solutions (Ribeiro et al 2018;Ahmad et al 2016). This is a result of the tendency of the acid to form hydrogen bonds with the IL in the liquid phase, protecting it from vaporization (Ribeiro et al 2018).…”
Section: Properties Of Superbase-based Ils During Thermal Recoverymentioning
confidence: 99%
“…Interestingly, although the acid has a higher volatility than the base, it was found that the base is more prone to vaporization from concentrated solutions (Ribeiro et al 2018;Ahmad et al 2016). This is a result of the tendency of the acid to form hydrogen bonds with the IL in the liquid phase, protecting it from vaporization (Ribeiro et al 2018). Under more drastic conditions, this phenomenon proceeds until an azeotropic composition is reached, where the system exhibits the best thermal stability (lowest vapor pressure) as noted in Figure 5 b (Baird et al 2020;Ribeiro et al 2018).…”
Section: Properties Of Superbase-based Ils During Thermal Recoverymentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen by the 1 [Ace] are in the 1:1 (cation:anion) proportion; the remaining are in the 1:2 (cation:anion) proportion due to the formation of an azeotrope during the distillation purification step. As reported by Ribeiro et al [25], mixtures of organic superbases with carboxylic acids lead to the formation of azeotropic mixtures with an acid/ base proportion different from the initially prepared 1:1. This happens due to the ability of carboxylic acids to form strong hydrogen bonds with the protic ionic liquid ion pair leading to an azeotropic composition rich in acid.…”
Section: Protic Ionic Liquid Synthesismentioning
confidence: 66%